Knowledge Graph Drawing: Westen Research on Chinese Communist Party (Journal of Interdisciplinary Insights, 2025)
Overseas research on the CCP has a long history and has accelerated since entering the new century. In combination with the fact that overseas research on the history and construction of the Chinese Communist Party as been listed as an important research direction of the first level discipline of the history and construction of the Communist Party of China, it is necessary to sort out and interpret overseas research on the Communist Party of China. This article is based on the scientometric tools CiteSpace and VOSviewer to draw a knowledge graph of English literature in the field published in the Science Citation Index (SSCI) and the Arts and Humanities Citation Index (A&HCI) from 2006 to 2024, making the research results more concrete. Research shows that the field is mainly focused on regional studies, with an overall increase in the number of publications. The research methods of the new generation of young scholars, including women, are more diverse, and empirical research that reflects the characteristics of the times, such as quantitative big data and qualitative interviews, has become the preferred choice for most researchers.